1999
DOI: 10.1002/1531-8249(199907)46:1<62::aid-ana10>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomographic measurement of acetylcholinesterase activity reveals differential loss of ascending cholinergic systems in Parkinson's disease and progressive supranuclear palsy

Abstract: We measured brain acetylcholinesterase activity in 16 patients with Parkinson's disease (PD), 12 patients with progressive supranuclear palsy (PSP), and 13 age‐matched controls, using N‐methyl‐4‐[11C]piperidyl acetate and positron emission tomography. Kinetic analysis was performed to calculate k3, an index of acetylcholinesterase activity. In PD patients, there was a significant reduction (−17%) of cerebral cortical k3 compared with normal controls, whereas there was only a nonsignificant reduction (−10%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(29 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…In vivo imaging studies have also shown that the presence of dementia in PD is associated with more severe and widespread cholinergic denervation compared with PD without dementia (Bohnen et al, 2003;Hilker et al, 2005;Kuhl et al, 1996;Shinotoh et al, 1999). These imaging results are consistent with post-mortem evidence that basal forebrain cholinergic system degeneration appears early in PD and worsens in parallel with the appearance of dementia (Ruberg et al, 1986).…”
Section: Heterogeneity Of Cholinergic Denervation In Pd and Clinical supporting
confidence: 74%
See 1 more Smart Citation
“…In vivo imaging studies have also shown that the presence of dementia in PD is associated with more severe and widespread cholinergic denervation compared with PD without dementia (Bohnen et al, 2003;Hilker et al, 2005;Kuhl et al, 1996;Shinotoh et al, 1999). These imaging results are consistent with post-mortem evidence that basal forebrain cholinergic system degeneration appears early in PD and worsens in parallel with the appearance of dementia (Ruberg et al, 1986).…”
Section: Heterogeneity Of Cholinergic Denervation In Pd and Clinical supporting
confidence: 74%
“…In contrast to severe striatal dopaminergic terminal losses, exceeding 50% to 80% in PD subjects with clinically manifest motor symptoms Guttman et al, 1997), in vivo acetylcholinesterase studies show cholinergic projection losses in the magnitude of 5% to 25% in PD subjects without or with dementia (Bohnen et al, 2003;Hilker et al, 2005;Shimada et al, 2009;Shinotoh et al, 1999). The more limited and variable cholinergic losses suggest the presence of overlap in cholinergic projection system integrity between PD and control groups.…”
Section: Introductionmentioning
confidence: 95%
“…22 The same authors reported a greater loss of thalamic AChE activity (Ϫ38%) in patients with progressive supranuclear palsy (PSP). The much higher incidence of falls in PSP compared to PD may reflect the more prominent degree of thalamic cholinergic denervation and PPN pathology in PSP.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of thalamic cholinergic denervation in PSP is further emphasized by the relatively preserved cortical cholinergic innervation in this disorder compared to PD. 22 In PSP patients, experimental administration of the antimuscarinic drug scopolamine has been reported to worsen gait in a dose-dependent manner. 23 Although scopolamine worsened gait functions, it did not negatively affect UPDRS motor ratings of bradykinesia or rigidity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation